Level up ! : the guide to great video game design. - Rogers, Scott, ....- (Chichester : Wiley, 2010)
Want to design and build cutting edge video games? Not sure where to start? Or just want to tweak the projects you're already working on? Then this is the book for you! Written by leading video game expert Scott Rogers, who has designed the hits; Pac Man World, God of War, Maxim vs. army of Zin and SpongeBob Squarepants. This book is full of Rogers' wit andimaginative style which demonstrates everything you need to know about designing great video games. Level Up! has been written with all levels of game designers in mind.From beginner level through to the more experienced game designer. It covers the entire video game creation process, allowing you to learn: How to develop marketable ideas What perils and pitfalls await them during a game's pre-production, production and post-production stages Creative ideas to serve as fuel for your own projects from game theme and environments to gameplay mechanics All in all it's an indispensible guide for video game designers both 'in the field' and the classroom. Other topics covered: Understanding what gamers want Compelling character design Working with player actions Techniques for non-human characters Camera techniques - the camera as a character Designing UI and HUD Use level design to tell game's story What game designers can learn from theme parks Combat, puzzles and game mechanics Fun and UNFUN How to make the world's greatest Boss battle (and why not to do it) and tons more - including the business of design, creating design documents, the pitch and more. The book alsocontains templates to create your ownpitch anddesign documents.